Teoremas de fatoração para operadores somantes - Lima, Alexandre César Bispo (2023)
Pietsch's Factorization Theorem is one of the main results of the Theory of absolutely summing Operators. This work aims to study some classes of linear and multilinear operators, in a certain abstract context, that satisfy a Pietsch-type Factorization theorem. As a result, we will present a factorization for the (p; σ)-absolutely continuous linear operators, and dominated (p1, . . . , pm; σ)-continuous and factorable strongly (p; σ)-summing multilinear operators.